Leading issues in Bangladesh development - Ahmed, Sadiq (Dhaka: University Press Limited, 2012)
Contributed articles.
Includes bibliographical references.
Keywords: Economic development -- Bangladesh; Economics; Bangladesh -- Economic conditions -- 21st century